SYSTEMATIC REVIEW AND META-ANALYSIS OF ASSOCIATION OF Î²2-ADRENERGIC RECEPTOR GENE POLYMORPHISMS WITH NOCTURNAL ASTHMA - Khan, Ihsanullah; Ul Haq, Zia; Shaheen, Asmat; Afridi, Mukhtiar Zaman; Ahmad, Nafees; Abassi, Rashda; Ahmad, Nasir; Siraj, Sami (Journal of Postgraduate Medical Institute, 2017)
Objective: To integrate the quantitatively existing evidences on nocturnal asthma and their association with Î²2-adrenergic receptor (Arg16Gly and Glu27Gln) polymorphism. Methodology: The whole procedure for systematic review and meta-analysis was conducted following PRISMA guidelines. The following databases Ovid, PubMed, Wiley online library, Springer link and the Web of Knowledge were searched for relevant articles. Random effect meta-analysis was conducted. Heterogeneity was evaluated by I2 statistic. The funnel plots and the Eager tests were used to assess the small study biases and potential publications. Results: This systematic review and meta-analysis comprised a total of 9 studies. The brief statement estimates suggested heterozygous Arg/Gly (OR =2.32; 95% CI =1.53-3.54; P value =<0.001), homozygous Gly (OR =4.78; 95% CI =2.60- 8.77, P-value =<0.001) and Gly allele (OR =1.71, 95% CI =1.14-2.56, P-value =0.009) was significantly associated with nocturnal asthma. While Glu27Gln polymorphism did not showed significant association with nocturnal asthma both in genotype (OR =1.28; 95% CI =0.63-2.59; P-value =0.496) and allelic (OR =1.65; 95% CI =0.64-4.27; P-value =0.301) analysis. Conclusion: Heterozygous Arg/Gly, homozygous Gly/Gly and Gly Allele were found to be significantly associated with nocturnal asthma.